Influence of ulceration etiology on the global quality of life and its specific dimensions, including the control of pain, in patients with lower limb vascular insufficiency - Cwajda-Białasik, Justyna; Szewczyk, Maria T.; Mościcka, Paulina; Jawień, Arkadiusz; Ślusarz, Robert (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction : The results of previous studies suggest that the quality of life in patients with lower limb ulcerations is markedly poorer than in the general population – with regard to physical, mental and social spheres. This complex character of that parameter necessitates comprehensive analyses of its specific aspects, including the level of the acceptance of illness and associated pain symptoms. Aim : To compare the quality of life and its specific dimensions in patients with lower limb ulcerations of various etiology. Material and methods : Patients with the ulcerations resulting from venous (n = 101) or arterial pathologies (n = 98), or having mixed etiology (n = 99) were examined with the: 1) Skindex-29 instrument, 2) Acceptance of Illness Scale, 3) Beliefs about Pain Control Questionnaire, and 4) Coping Strategy Questionnaire. Results : The average quality of life related to physical symptoms was significantly higher in patients with venous ulcerations. Patients with ulcerations of arterial etiology more frequently used catastrophizing, and less often ignored pain sensations, used coping self-statements, and increased their activity levels; they were characterized by lower levels of control and poorer ability to decrease the pain. The internal locus of pain control increased proportionally to the global quality of life scores and levels of illness acceptance. Control over pain and ability to decrease the pain were more effective in individuals who used ignoring pain sensations, increasing the activity level, coping self-statements, and reinterpreting pain than in those using catastrophizing or praying and hoping strategies. Conclusions : Physical complaints seem to be the basic determinant of the quality of life in patients with the lower limb ulceration, irrespective of its etiology.